KONSEP TADABBUR AL-QUR’AN PERSPEKTIF TOKOH DA’WAH SYAIKH IBNU ‘ASYUR - Aan Handriyani (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2026)
This research aims to describe the concept of tadabbur (reflection) through the perspective of Muhammad al-Tahir ibn Ashur in his monumental work, Tafsir al-Tahrir wa al-Tanwir. As an innovative contemporary commentary, this work offers a unique methodological approach to understanding the Qur'an. This study employs a content analysis method with a thematic approach (mawdhu’i) toward the verses related to tadabbur within the text. The findings reveal that Ibn Ashur’s concept of tadabbur is a model of intensive, profound, and continuous interaction with the Qur'an. This activity involves the optimization of both the intellect and the heart (i’mâl an-nazhr al-‘aql) to contemplate the Qur'anic guidance (dilâlah), thereby uncovering various truths and sciences, encompassing both tadabbur dilâlah tafshîly (detailed) and tadabbur ijmâly (global). Furthermore, this study concludes that tadabbur is the primary means to attain the blessings of the Qur'an, while its neglect leads to misguidance. Ibn Ashur identifies the Ulul Albâb (people of understanding) as the subjects capable of performing tadabbur, whereas the primary obstacles are ignorance and a locked heart (aqfâl).